Laparoscopic ureterolithotomy and retrograde flexible ureteroscopy-assisted transperitoneal laparoscopic ureteroureterostomy for a huge ureteropelvic junction stone and multiple small renal stones: A CARE-compliant case report. Issue 28 (16th July 2021) - Chou, Sheng-Feng; Hsieh, Po-Fan; Lin, Wei-Ching; Huang, Chi-Ping
Abstract: Rationale: Concurrent kidney and ureteral stones are always complicated and a clinical challenge. Improvements in endoscopic equipment have led to the widespread adoption of retrograde intrarenal surgery, which has a good stone clearance rate. On the other hand, laparoscopic ureterolithotomy (LUL) has been reported to be non-inferior to retrograde flexible ureteroscopy in stone-free rate and the need for axillary procedures, and to have a significantly lower rate of post-operative sepsis compared to retrograde flexible ureteroscopy. We describe a case managed with LUL followed by laparoscope-assisted retrograde intrarenal surgery (LA-RIRS) in a single operation for a large upper ureteral stone and small renal stones, which is usually challenging and requires axillary procedures. Patient concerns: The patient was a 66-year-old male with underlying hypertension and diabetes mellitus. He reported severe flank pain after receiving endoscopic management of concurrent right ureteropelvic junction stone and multiple renal stones about 1 month previously. Diagnosis: The residual stones were reassessed using non-contrast computed tomography before surgery. A 2.8-cm residual ureteropelvic junction stone and multiple renal stones with a maximum length of 1 cm were found. A second operation was considered to be necessary due to the deterioration of his renal function and refractory flank pain. Interventions: We performed LUL followed by LA-RIRS. Two surgeries were completed in a single operation. The Jackson–Pratt drain was removed 3 days after the operation. Outcomes: After the surgery, no high-grade complications were recorded according to the Clavien Dindo classification. A follow-up kidney, ureter, and bladder radiograph performed 2 months after the operation revealed no residual stones. Renal echo revealed no obstructive nephropathy 1 month after double-J catheter removal. Conclusion: LUL with LA-RIRS with a stone basket for renal stone extraction is a safe and feasible technique, and no step surgery or axillary procedures were needed in our case. If clinical cases with a huge stone burden over the ureter are indicated for LUL with concurrent small renal stones, LUL with LA-RIRS can be an alternative option.